IT PROCESS OPTIMIZATION THROUGH THE IMPLEMENTATION OF BIMODAL IT WITH DEVOPS - Charles do Nascimento Marreiros, Emerson; José Galvão do Nascimento, Esrom (Journal of Interdisciplinary Debates, 2024)
In recent years, changes have been made in the development of information systems software for a more agile way of working. Agile teams are responsible for obtaining requirements in a multidisciplinary set, where the business part and the development part are represented in a single project. DevOps is a new movement that tries to improve agility in service delivery. It encourages greater collaboration and communication between development teams and operations and prevents problems and operational needs from being exposed in the project, affecting software quality. For large and cross-platform businesses, it is essential to consider the mainframe in these tool chains because data and mainframe applications are among their strategic digital assets. The ideal architecture for mainframe inclusion harmoniously combines the specificity of the well-integrated mainframe / task platform (DevOps) into the broader environment of the development and operations chain. Inclusive tooling chains generate a significant competitive advantage by enabling you to have quality information from the mainframe code, making the platform much more accessible to DevOps equipment. Thus, the main problem of the work is: what are the main benefits that would lead a company’s IT area to invest in the implementation of bimodal IT with DevOps, aiming to optimize processes?